2011
DOI: 10.4061/2011/980150
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Genomic Analysis of Sézary Syndrome

Abstract: Sézary syndrome (SS) is a rare variant of primary cutaneous T-cell lymphoma. Little is known about the underlying pathogenesis of S. To address this issue, we used Affymetrix 10K SNP microarray to analyse 13 DNA samples isolated from 8 SS patients and qPCR with ABI TaqMan SNP genotyping assays for the validation of the SNP microarray results. In addition, we tested the impact of SNP loss of heterozygosity (LOH) identified in SS cases on the gene expression profiles of SS cases detected with Affymetrix GeneChip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Specifically, point mutations, focal deletions, and translocations of NFIA have been found in myeloproliferative neoplasms [114,115] and acute erythroid leukemia [116] (Table 3). Loss of NFIB due to 9p LOH was also reported in approximately 30% of myeloproliferative neoplasms [117][118][119], and in T-cell lymphomas (Sézary syndrome) [120]. These findings suggest a possible role for NFI in hematopoietic tumour development, as corroborated for T-cell lymphomas in an insertional mutagenesis mouse model where insertions within Nfia, Nfib and Nfic occur [121] (Table 2a).…”
Section: Hematopoietic Tumourssupporting
confidence: 56%
“…Specifically, point mutations, focal deletions, and translocations of NFIA have been found in myeloproliferative neoplasms [114,115] and acute erythroid leukemia [116] (Table 3). Loss of NFIB due to 9p LOH was also reported in approximately 30% of myeloproliferative neoplasms [117][118][119], and in T-cell lymphomas (Sézary syndrome) [120]. These findings suggest a possible role for NFI in hematopoietic tumour development, as corroborated for T-cell lymphomas in an insertional mutagenesis mouse model where insertions within Nfia, Nfib and Nfic occur [121] (Table 2a).…”
Section: Hematopoietic Tumourssupporting
confidence: 56%
“…11,[37][38][39] Indeed, data from our group 22,27 and from others [23][24][25][26]28,29,[40][41][42][43] showed the presence of more complex chromosome aberrations in aggressive CTCL than in C-ALCL. 28,44 When telomeres become critically short, it is believed that their protective function is compromised and that cells follow the flow diagram process (Figure 7) with replicative senescence, crisis, escape from crisis, and maintenance of TL.…”
Section: Discussionmentioning
confidence: 59%
“…To answer this question, genomic abnormalities were investigated in SS patient cells and cell lines, taking into consideration chromosome aberrations previously reported in SS patients by our group 27 and others. [23][24][25][26]28,29 For cases 2 and 17, AU (data not shown), c-MYC and centromere 8 fluorescent probes were chosen to investigate SS nuclei chromosomal status in combination with antibodies to delineate SS cells ( Figure 2E-H) or with peptide nucleic acid telomeric probes to evaluate TL ( Figure 2I-J). Image analysis revealed that abnormal chromosome content was restricted to both neoplastic SS T cells ( Figure 2E-H) and to nuclei with short telomeres, whereas cells with normal chromosome content showed long telomeres ( Figure 2I-J).…”
Section: Short Tl: a Hallmark Of Neoplastic Ss Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…A low resolution 10K SNP array of eight patients with SS identified frequent SNP copy number changes and LOH involving 1, 2p, 3, 4q, 5q, 6, 7p, 8, 9, 10, 11, 12q, 13, 14, 16q, 17, and 20 [126]. SNP copy number loss was most frequent at FAT gene at 4q35 (75%), followed by VEGFC at 4q34.1q34.3 (50%), NFIB at chromosome 12 (38%), and TRIM16 at 17p11.2 (38%).…”
Section: Mature T/nk-cell Lymphoproliferative Disordersmentioning
confidence: 99%